Parsing the IL-37-Mediated Suppression of Inflammasome Function - Ina Rudloff; Holly K. Ung; Jennifer K. Dowling; Ashley Mansell; Laura D’Andrea; Andrew M. Ellisdon; James C. Whisstock; Philip J. Berger; Claudia A. Nold-Petry; Marcel F. Nold (Cells, 2020)
Interleukin (IL)-37 is a member of the IL-1 family of cytokines. Although its broad anti-inflammatory properties are well described, the effects of IL-37 on inflammasome function remain poorly understood. Performing gene expression analyses, ASC oligomerization/speck assays and caspase-1 assays in bone marrow-derived macrophages (BMDM), and employing an in vivo endotoxemia model, we studied how IL-37 affects the expression and maturation of IL-1β and IL-18, inflammasome activation, and pyroptosis in detail. IL-37 inhibited IL-1β production by NLRP3 and AIM2 inflammasomes, and IL-18 production by the NLRP3 inflammasome. This inhibition was partially attributable to effects on gene expression: whereas IL-37 did not affect lipopolysaccharide (LPS)-induced mRNA expression of Il18 or inflammasome components, IL-37-transgenic BMDM displayed an up to 83% inhibition of baseline and LPS-stimulated Il1b compared to their wild-type counterparts. Importantly, we observed that IL-37 suppresses nigericin- and silica-induced ASC oligomerization/speck formation (a step in inflammasome activation and subsequent caspase-1 activation), and pyroptosis (−50%). In mice subjected to endotoxemia, IL-37 inhibited plasma IL-1β (−78% compared to wild-type animals) and IL-18 (−61%). Thus, our study adds suppression of inflammasome activity to the portfolio of anti-inflammatory pathways employed by IL-37, highlighting this cytokine as a potential tool for treating inflammasome-driven diseases.